Inequality, household debt, ageing and bubbles: A model of demand-side Secular Stagnation - Stefano Di Bucchianico (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2021)
The mainstream concept of Secular Stagnation provides a comprehensive theoretical picture to explain sluggish economic growth and engenders a renewed role for fiscal policy. For these reasons, it should be praised. Given the difficulties entailed by the theoretical framework in which the theory is located, this paper offers a perspective on US stagnation that is grounded in some of the same foundational elements of the mainstream attempt (inequality, sluggish population growth and ageing, household debt, housing bubble) but relies on a model in which growth is driven by the autonomous components of aggregate demand. Stagnation is the result of the failure to move from a household debt-plus-bubble-led model to a model led by public expenditure. In the course of the analysis, a new treatment of ageing is offered.
Keywords: E31; E40; E52; E58; 330; Secular Stagnation; natural rate of interest; fiscal policy; aggregate demand; supermultiplier